2020
DOI: 10.1109/tmrb.2020.3025364
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Hand Motor Imagery Tasks Within the Same Limb From EEG Signals Using Deep Learning

Abstract: Motor imagery (MI) tasks of different body parts have been successfully decoded by conventional classifiers, such as LDA and SVM. On the other hand, decoding MI tasks within the same limb is a challenging problem with these classifiers; however, it would provide more options to control robotic devices. This work proposes to improve the hand MI tasks decoding within the same limb in a brain-computer interface using convolutional neural networks (CNNs); the CNN EEGNet, LDA, and SVM classifiers were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Finally, as mentioned above, the electrotactile was used with EMG in closed-loop systems. Alternatively, the study of Achanccaray and Hayashibe, (2020) integrated electrotactile feedback with BCI, where an improved motor imagery, and significant improvements in flexion and extension were observed [66]. Given that flexion and extension are the main movements in grasping, the results of this study indicate that electrotactile with BCI systems may show benefits comparable to closed-loop systems.…”
Section: Prosthesesmentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, as mentioned above, the electrotactile was used with EMG in closed-loop systems. Alternatively, the study of Achanccaray and Hayashibe, (2020) integrated electrotactile feedback with BCI, where an improved motor imagery, and significant improvements in flexion and extension were observed [66]. Given that flexion and extension are the main movements in grasping, the results of this study indicate that electrotactile with BCI systems may show benefits comparable to closed-loop systems.…”
Section: Prosthesesmentioning
confidence: 77%
“…4) for stimulating the upper arm, they also observed that the individuals with amputations showed significant improvements in differentiating materials with diverse level of stiffness [79]. Of note, in contrast with the above mentioned studies, which implemented a closed-loop between EMG and electrotactile feedback, the study of Achanccaray and Hayashibe, (2020) implemented the electrotactile feedback in combination with a brain-computer-interface (BCI), where the latter was controlling the prosthetic's movements and actions [66]. Comparably to the closed-loop systems, their study revealed that the conjunction of BCI and electrotactile feedback facilitates a substantially improved motor imagery, and significant improvements in flexion and extension, which are the essential grasping movements [66].…”
Section: Biomedical Applications: Prosthesesmentioning
confidence: 99%
“…The Common Spatial patterns technique is probably the most commonly used spatial filtering technique in BMIs [34][35][36]. This method is applied mainly to binary classification; it consists in computing a transformation matrix W that is maximizing the variance of the signal for one class while minimizing it for the other [37].…”
Section: A) Common Spatial Patterns (Csp)mentioning
confidence: 99%
“…e CSP method is based on the calculation of a transformation matrix W (equation ( 1)) that maximizes the variance of spatially filtered EEG data belonging to one class while minimizing it for the other class: in our case, EEG data of MI tasks of the left and right limbs. e matrix X is transformed into a matrix Z. W is a square matrix, the dimensions of which depend on the number of channels, and its columns are [11,[41][42][43].…”
Section: Experimental Procedurementioning
confidence: 99%
“…e SVM classifier has demonstrated to be efficient for discriminating between two motor-imagery classes, and it is the standard classification method used for binary-class BCIs based on MI owing to its fast and computationally efficient training [43][44][45]. An SVM classifier was trained to discriminate between the left and right limbs for the grasping and flexion/extension MI tasks.…”
Section: Experimental Procedurementioning
confidence: 99%